Die Altertumswissenschaften an der Preußischen Akademie der Wissenschaften in der Zeit von U. von Wilamowitz-Moellendorff (1848–1931), A. von Harnack (1851–1930) und E. Meyer (1855–1930) - Rebenich, Stefan (Hyperboreus, 2014)
The article deals with the organisation and development of Classical studies in the Berlin Academy of Sciences at the turn of the 19th century, and of subsequent changes in its science policy after World War I and the October Revolution in Russia. In addition, the author focuses on the contact between Russian Classical scholars and the Berlin Academy of Sciences in the 1920s.